Effects of White Turmeric Infusion on the Liver Cells in Carbon Tetrachloride-Induced Mice - Oktaviani, Fitria; Herdiningrat, RB. Soeherman; Yulianti, Herry (Althea Medical Journal, 2015)
Background: The liver is an organ that has important functions in the body. Liver damage can be causedÂ by oxidative stress and free radicals. White turmeric (Curcuma zedoaria L) contains antioxidants that canÂ be used to neutralize the effects of free radicals. This study was conducted to determine the effect of whiteÂ turmeric infusion on histological appearance of liver cells in male mice induced by carbon tetrachlorideÂ (CCl4).Methods: This laboratory experimental study was conducted using male mice (Mus musculus) with Balb/cÂ strain. Thirty-three mice were randomly divided into 3 groups i.e.,group 1 as a control group was givenÂ standard food and drink, group 2 was given 10% of CCl4 0.1 ml by intraperitoneal injection on the firstÂ day and group 3 was given 10% of CCl4 0.1 mL by Â ntraperitoneal injection on the first day, followed by theÂ administration of 50% of white turmeric infusion 0.2 mL. Kruskal-Wallis test method was used to analyseÂ the significant differences of the average percentage of damaged liver cells in the group given CCl4 aloneÂ with the group given CCl4 and white turmeric infusion and control group.Results: The percentage of damaged liver cells between groups of mice given CCl4 alone and the groupÂ given CCl4 followed by white turmeric infusion were respectively(p <0.05) compared to group1.Conclusions: Administration of white turmeric infusion gave an influence by decreasing the percentage ofÂ damaged liver cells in CCl4-induced mice. White turmeric can serve as an alternative antioxidants that canÂ be used to neutralize the effects of free radicals. [AMJ.2015;2(4):506â10]Â DOI:Â 10.15850/amj.v2n4.498